Concentration and temperature dependence of the viscosity of polyol aqueous solutions - Longinotti, María Paula (2014)
The concentration and temperature dependence of the viscosity of supercooled polyol (sucrose, trehalose, glucose and glycerol) aqueous solutions was analyzed with the aim of finding simple and accurate correlation equations for the description of this transport property. Three different equations were examined and compared, two empirical equations and an equation derived from the Avramov–Milchev (AM) model. If a description of the viscosity temperature dependence is intended, the AM model gives the best representation of the experimental data with only two adjustable parameters, which have a clear physical meaning. However, if we focus on both, temperature and concentration dependence, the empirical equations are found to be superior to the AM model, except for the glycerol aqueous system. The AM model includes a parameter related to the system fragility, which was obtained for all the aqueous polyol mixtures previously mentioned as a function of concentration, and also for water–trehalose–sodium tetraborate mixtures as a function of the electrolyte content. The results show that the fragility parameter increases with polyol concentration in the series glycerol < glucose ∼ sucrose < trehalose, and that the addition of sodium tetraborate to aqueous trehalose solutions increases the fragility of the mixtures. Our results imply that the hypothesis relating the low fragility of the aqueous mixtures with their high cryo or dehydroprotection capabilities is not valid.